Handbook of Assessment and Treatment of Eating Disorders - Walsh, B. Timothy (American Psychiatric Publishing, 2015)
Chapters on assessment and treatment, along with accompanying videos, offer comprehensive, state-of-the-art coverage that will benefit clinicians in practice, such as psychiatrists and psychotherapists, as well as mental health trainees.